Abortion-prevention Behaviour Among Adolescents at Nuruddin Islamic Boarding School, Sungai Sarik Village - Ani Triana; Nelly Karlinah; Yulrina Ardhiyanti; Hetty Ismainar (Media of Health Research, 2026)
Abortion is often perceived as a common issue among adolescents due to its frequent portrayal in electronic and print media. Abortion-prevention behavior refers to actions aimed at preventing abortion and its associated adverse health consequences. At Nuruddin Islamic Boarding School, reproductive health education and counseling on abortion prevention had not been provided by healthcare professionals. This study aimed to identify factors associated with abortion-prevention behavior among students at Nuruddin Islamic Boarding School in Sungai Sarik Village. A quantitative study with an analytical cross-sectional design was conducted among 100 students selected through systematic random sampling from a population of 121 students. Data were analyzed using univariate and bivariate (Chi-square test) analyses, and multivariable logistic regression. The findings revealed that 58% of respondents demonstrated poor abortion-prevention behavior. Multivariable logistic regression analysis showed that attitude (p = 0,011), knowledge (p = 0,012), and the role of healthcare providers (p = 0,016) were significantly associated with abortion-prevention behavior. Among these factors, attitude emerged as the most influential predictor. Attitude, knowledge, and the role of healthcare providers were significant determinants of abortion-prevention behavior among adolescents. Strengthening positive attitudes, improving reproductive health knowledge, and increasing healthcare provider involvement in reproductive health education and counseling may enhance abortion-prevention behavior and contribute to reducing the risk of unintended pregnancy and unsafe abortion among adolescents.